Invisible - Steel, Danielle (New York : Random House Large Print, 2022)
Antonia Adams is the product of a loveless marriage between a beautiful young model and an aristocrat. Unprotected and unloved, she learns that the only way to feel safe is to hide from the dangers around her. Her love of the movies turns into a dream to become a screenwriter, and a summer job at a Hollywood studio. There, a famous British filmmaker notices her, and suddenly she can remain invisible no longer. He wants to put her in a movie and make her a star. When tragedy strikes, she must decide whether she will remain centre stage or become invisible again, where she feels safest.
Keywords: Actors -- Fiction; Screenwriters -- Fiction; Motion picture producers and directors -- Fiction; Man-woman relationships -- Fiction; New York (N.Y.) -- Fiction; Romance fiction; Large type books